Why so nervous? Revisiting the sources of speech anxiety in Chinese as a second language. (December 2021) - Sun, Peijian Paul; Teng, Lin Sophie
Abstract: This study examined the linguistic and extra-linguistic sources of speech anxiety of second/foreign language (L2) learners of Chinese through a structural equation modeling approach. Data were collected from 226 L2 learners of Chinese via questionnaires and speaking tests. Three competing models were proposed to understand how linguistic (i.e., speech proficiency) and extra-linguistic (i.e., willingness-to-communicate/WTC, socio-cultural attitudes, speech strategies, and speech self-efficacy) factors jointly influenced learners' L2 Chinese speech anxiety. The results of model comparisons suggested that 1) speaking strategies were the most positive predictor directly contributing to speech anxiety; 2) the other significant direct predictors included WTC, speaking self-efficacy, and speaking proficiency; 3) socio-cultural attitudes had a positive indirect effect on speech anxiety through the mediation of WTC. The study concluded with pedagogical implications on how to ameliorate students' L2 Chinese speech anxiety in classroom teaching.